Factors affecting grazing preference by sheep in a breeding population of tall fescue (Festuca arundinacea Schreb.). (19th December 2017) - Cougnon, M.; Shahidi, R.; Schoelynck, J.; Van Der Beeten, I.; Van Waes, C.; De Frenne, P.; Van Labeke, M.‐C.; Reheul, D.
Abstract: A disadvantage of tall fescue ( Festuca arundinacea Schreb.) is its low voluntary intake, resulting in suboptimal performance under grazing. Ideally, selection for this trait is done using grazing animals, but their use in plant breeding programmes is costly and laborious. Repeatable, stable and quantifiable traits linked to animal preference could ease tall fescue breeding. We established a trial to find relationships between the grazing preference of sheep and sward‐ and plant‐related traits. Seventeen genotypes were studied in swards. Sheep grazing preference, pre‐grazing sward height (SH), leaf softness, leaf blade length, width, colour and shear strength, and concentration of fibre, silica, digestible organic matter (DOM) and water‐soluble carbohydrate (WSC) were quantified throughout the growing season. The traits with the strongest correlation with sheep preference were DOM, SH, leaf colour, leaf width and WSC. Leaf softness, silica content and leaf shear strength were not correlated with sheep preference. We conclude that DOM is the trait that offers the best prospects for contributing to progress in tall fescue plant breeding for both intake and feeding value.